(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the problem of illicit trafficking in narcotic drugs and psychotropic substances as well as their zloutrebleniya to date according to the researcher most aktual.Onaaffects all levels of society and the country word.The-first drug problem is closely connected with the general increase in crime,including crime related with them. Key words: i international criminal law, the principle of the inviolability of diplomatic agents, diplomatic immunity, crime prevention, security.